(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background and Aim- There is a paucity of high-quality evidence concerning mesh choice in open inguinal hernia repair. Using an expertise-based quality of life scale, we aimed to evaluate the postoperative impact of two different mesh types on pain and discomfort, quality of life. Methods- This observational cohort study's with retrospective analysis. Based on the inguinal hernia laparoscopic each patient underwent between January 2021 and December 2022, (2 years) two patient cohorts were created conducted at tertiary care hospital. One group of surgeons used a heavyweight polypropylene mesh (90 g/m2, Bard™ Flatmesh, Davol) while the second group employed a lightweight mesh (28 g/m2, ULTRAPRO™, Ethicon). A total of 360 hernia patients were admitted during the study period and among them random allocation was done for 180 patients was used with Heavyweight mesh (HWM) and 180 for lightweight mesh (LWM). Results- Mean age group was 58 years in Heavy weight mesh and 59.4 years in low weight mesh. Mean BMI was 25. Most of the patients had indirect hernia followed by direct hernia. Comparing the study groups, there were significant differences (p<0.05) concerning awareness of a groin lump and groin discomfort, while close to significance regarding perception of foreign material, favouring the lightweight group 1 year after surgery. No statistically significant difference in quality of life as measured by EQ-5D between the different mesh groups could be detected. In total, expressed by minimally important differences, 152/180 in heavyweight mesh group patients (48.2%; 95% CI 42.8–53.6) improved their quality of life. The outcomes for quality of life based on Caroline comfort scale, no significant differences could be observed between the 2 groups. Conclusion- Two year following Laparascopic surgery, there were noticeable changes in the awareness of a groin lump and discomfort, favouring the lighter group, but no difference in quality of life could be demonstrated between the groups in the trial's heavyweight and lightweight mesh groups.